Implementación de un prototipo de alarma de parto bovino para la finca Jaicar - Hidalgo-Arias, Josué (Instituto Tecnológico de Costa Rica, 2018)
This report presents the design and implementation of a prototype to detect typical patterns of movement in cows close to give birth and generate an alarm based on that data. A contraction detector algorithm is presented, which uses the angles: pitch, roll and yaw to make a delivery estimate.
Proyecto de graduación (Licenciatura en Ingeniería Electrónica). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018.
Keywords: Producción animal; Partos; Gestación; Dispositivos electrónicos; Microcontroladores; Software; Bovinos; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Agronomy